Optimization of operating factors and blended levels of diesel, biodiesel and ethanol fuels to minimize exhaust emissions of diesel engine using response surface methodology. (25th April 2016) - Khoobbakht, Golmohammad; Najafi, G.; Karimi, Mahmoud; Akram, A.
Highlights: Biodiesel and ethanol reduced CO, HC, NOx, smoke opacity and increased CO2 . RSM can be employed to optimize engine performance and exhaust emissions. A high desirability was obtained as 74% by RSM. High desirability was detected at 2800 rpm, 63% diesel, 26% biodiesel and 11% ethanol blends. Optimum parameters were 0.013% of CO, 41 ppm of HC, 643 ppm of NOx, 12% of smoke opacity and 7.3% of CO2 . Abstract: This study is aimed at investigating the effect of operating factors of engine load and speed as well as blended levels of biodiesel and ethanol in diesel fuel on the emission characteristics of DI diesel engine. The experiments were designed using a statistical tool known as Design of Experiments (DoE) based on central composite rotatable design (CCRD) of response surface methodology (RSM). The resultant quadratic models of the response surface methodology were helpful to predict the response parameters such as oxides of nitrogen (NOx), carbon monoxide (CO), carbon dioxide (CO2 ) and total hydrocarbon (THC) and smoke opacity and further to identify the significant interactions between the input factors on the responses. The results depicted that biodiesel and ethanol could reduce CO and HC emissions as well as smoke opacity and enhance CO2 which indicated a more quality in fuel combustion. However over adding these biofuels in diesel led their detrimental impacts to be dominant over advantages of biodiesel and ethanol and as result emissions tended to increase. Optimization of independent variables was performed using the desirability approach of the response surface methodology with the goal of minimizing CO, THC, NOx and smoke opacity and maximizing CO2 . An engine load of 80% of full load bar, speed of 2800 rpm and a blend of 26% biodiesel, 11% ethanol and 63% diesel were found to be optimal values with a high desirability of 74% for the test engine having 0. 013% of CO, 41 ppm of HC, 643 ppm of NOx, 12% of smoke opacity and 7.3% of CO2 .